RANCANG BANGUN THERMAL ANEMOMETER DENGAN KONTROL PROPOSIONAL INTEGRAL - Muhamad Yusuf (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2015)
Maintaining the stability of the air at the speed of pressurized pipe used for gas distribution lines are very unlikely to do the kind of windmill anemometer, cup anemometer and other tipes. One tipe of measuring instruments in accordance with these conditions is Thermal Anemometer. Thermal anemometer is a wind speed measuring devices that use temperature change, then converted to a change in wind speed with the help of the heater. This measure is widely used to measure the flow rate / pressure pa wind in the PI. Price of this measure is relatively very expensive. In this study, the configuration between the temperature sensor LM 35 with heater elements in the form of solder 40W to measure wind speed. Temperature sensor has a relatively slow response time mainly fall time. To overcome this would be to use Proportional Integral Controller so that the resulting response time is faster. LM35 sensor configuration with proportional and integral controller is capable of measuring a maximum wind speed of 6.9 m / s.